Comparison of water and terrestrial jumping in natural and robotic insects - Koh, Je Sung; Baek, Sang Min; Kim, Baekgyeom; Cho, Kyu Jin; Kim, Ho Young (Annals of the New York Academy of Sciences, 2024)
Jumping requires high actuation power for achieving high speed in a short time. Especially, organisms and robots at the insect scale jump in order to overcome size limits on the speed of locomotion. As small jumpers suffer from intrinsically small power output, efficient jumpers have devised various ingenuous schemes to amplify their power release. Furthermore, semi-aquatic jumpers have adopted specialized techniques to fully exploit the reaction from water. We review jumping mechanisms of natural and robotic insects that jump on the ground and the surface of water, and compare the performance depending on their scale. We find a general trend that jumping creatures maximize jumping speed by unique mechanisms that manage acceleration, force, and takeoff duration under the constraints mainly associated with their size, shape, and substrate.
Keywords: Animals; Biomechanical Phenomena; Insecta; Locomotion; Robotics; Water; jumping insects; jumping mechanisms; jumping on water; robotic insects